1993
DOI: 10.1126/science.8475386
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TCR Signaling by CD45 Lacking Transmembrane and Extracellular Domains

Abstract: The CD45 protein is a transmembrane tyrosine phosphatase that is required for normal T cell receptor (TCR)-mediated signaling. A chimeric complementary DNA encoding the intracellular enzymatically active portion of murine CD45 preceded by a short amino-terminal sequence from p60 c- src was transfected into CD45- T cells. Expression of this chimeric protein corrected most of the TCR signaling abnormalities observed in the absence of CD45, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 24 publications
6
75
0
Order By: Relevance
“…Using CD45-deficient cell lines and CD45 gene-disrupted mice, it has been shown that CD45 functions as an important regulator of maturation and activation pathways in lymphocytes (1)(2)(3). The importance of the phosphatase activity of CD45 in lymphocyte activation has been confirmed by the finding that transfection of chimeric proteins containing the cytoplasmic domains of CD45 into cells deficient in CD45 expression restores normal T cell signaling events (4,5). Downstream substrates of CD45 have been identified as the protein tyrosine kinases p56 lck and p59…”
mentioning
confidence: 67%
“…Using CD45-deficient cell lines and CD45 gene-disrupted mice, it has been shown that CD45 functions as an important regulator of maturation and activation pathways in lymphocytes (1)(2)(3). The importance of the phosphatase activity of CD45 in lymphocyte activation has been confirmed by the finding that transfection of chimeric proteins containing the cytoplasmic domains of CD45 into cells deficient in CD45 expression restores normal T cell signaling events (4,5). Downstream substrates of CD45 have been identified as the protein tyrosine kinases p56 lck and p59…”
mentioning
confidence: 67%
“…Studies of CD45-deficient cell lines and CD45-deficient mice initially demonstrated an essential role for CD45 in TCR-mediated signal transduction as a positive regulator (25,26). However, recently, an unexpected function of CD45 has been reported: CD45 could negatively regulate cytokine receptor signaling (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transfection of the cytoplasmic domain of CD45 (containing tyrosine phosphatase activity) into CD45-negative cells was also able to moderately restore the migratory response, suggesting that CD45 phosphatase activity is important for mediating CXCL12-induced chemotactic signaling. The cytoplasmic domain of CD45 has also been shown to be required for TCR-mediated signaling events (22,23).…”
Section: Discussionmentioning
confidence: 99%